Adolescent sexuality education, sexual debut, and associated factors in Nigerian public secondary schools - Tope Michael Ipinnimo; Olalekan Oladipupo Rosiji; Olumide Temitope Asake; Oluwafunmilayo Oluwadamilola Ibikunle; Motunrayo Temidayo Ipinnimo; Toluwalope Motunrayo Asake (Scientific Reports)
Abstract Adolescents in Nigeria face significant sexual and reproductive health risks, yet the effectiveness of existing sexuality education programs remains uncertain. Addressing these gaps is critical to improving adolescent health outcomes. This study assessed sexuality education, sexual debut, and associated factors among public secondary school adolescents in Ekiti State, Nigeria. A cross-sectional study was conducted among 380 adolescents selected through multistage sampling. Data were collected using a validated semi-structured questionnaire covering sociodemographic variables, sexuality education (assessed with 13 questions exploring past sex-related discussions, sexually transmitted infection, contraceptive, and puberty), as well as engagement in sexual intercourse. Pearson chi-square and binary logistic regression were used to identify the predictors of engagement in sexual intercourse. Approximately 36.8% (n = 140) of respondents had a good level of sexuality education. Less than one-third, 27.1% (n = 103) had ever discussed sex-related matters with their parents or guardian. About 22.1% (n = 84) had engaged in sexual intercourse, with 41.7% (n = 35) having their sexual debut before the age of 15. Predictors of engagement in sexual intercourse included being ≥ 18 years old (AOR 12.881, 95% CI 3.615–45.892), male gender (AOR 2.573, 95% CI 1.353–4.892), senior secondary school enrollment (AOR 4.201, 95% CI 1.654–10.671), polygamous family background (AOR 2.508, 95% CI 1.007–6.316), having four or more siblings (AOR 3.778, 95% CI 2.043–6.986), and higher level of sexuality education (AOR 1.829, 95% CI 1.006–6.986). A huge proportion of adolescents who engage in sexual intercourse begin early; therefore, it is crucial to target interventions to address their needs at this stage. The limited parental involvement in sexuality education must be addressed to provide adolescents with safe, accurate, and socio-culturally sensitive comprehensive sexuality education. We suggest increasing advocacy to encourage parents and guardians to openly educate their children about sexuality.